Influence of Inhibition of Adenosine Uptake on the γ-Aminobutyric Acid Level of the Ischemic Rat Brain - Seif-El-Nasr, Mona; Khattab, Mahmoud (Arzneimittelforschung, 2002)
Loss of inhibitory GABAergic modulation may induce hyperexcitability of neuronal elements and potentiate their vulnerability to excitotoxic injury. It has been also found that the adenosine system interacts with the GABAergic system during ischemia and anoxia where the adenosine receptors as well as the GABAergic receptors may conscript the same intracellular pathway to increase tolerance to ischemia. Therefore, it was aimed to study whether dipyridamole (CAS 58-32-2), an adenosine uptake inhibitor, or adenosine (CAS 58-61-7) could affect the rat brain γ-aminobutyric acid (GABA, CAS 56-12-2) level after induction of cerebral ischemia, and to test their effect on the lactate dehydrogenase (LDH) activity of the ischemic rat brain.Ischemia was induced by bilateral clamping of the common carotid arteries for 60 min followed by reperfusion for other 60 min. Dipyridamole was administered alone and in combination with adenosine and the effect of the drugs on the brain GABA level as well as on LDH activity was determined. The results show that dipyridamole could protect the brain of rats against the ischemic insult, while adenosine when administered separately failed to influence the selected parameters. Protection of the rat brain by dipyridamole might be related to the elevated level of GABA.
Keywords: Adenosine; γ-Aminobutyric acid; CAS 56-12-2; CAS 58-32-2; CAS 58-61-7; Dipyridamole; Ischemia